2020
DOI: 10.3390/agronomy10121896
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Root Architecture and Aboveground Traits of Red Clover Cultivars Driven by Breeding to Improve Persistence

Abstract: Red clover persistence has been one of the major targets for the most breeding programs worldwide. A phenotypic characterization at above- and belowground level was performed to a set of highly persistent red clover populations. The objective was to identify phenotypic changes occurring after empirical selection for plant survival, which is the consensus criteria of persistence. Eleven red clover populations were established on mesocosms of polyvinyl chloride (PVC) tubes of 11 cm in diameter and 100 cm depth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Root mesocosms, typically large horticultural pots or long narrow pipes form which the entire root system can be extracted, have proven useful in understanding RSA and root function of several agricultural species. For examples: it was reported that a lower number of crown roots in maize can be beneficial for nitrogen acquisition in poor nitrogen soils ( Saengwilai et al., 2014 ), a moderate progressive drought could lead to RSA adaptations in various rice cultivars that improve performance under reduced water management practices ( Hazman and Brown, 2018 ), some Green Revolution wheat progenitors have smaller root systems than older landraces ( Waines and Ehdaie, 2007 ), and Chilean red clover cultivars with certain RSA traits, such as high crown root diameter and low branching index, correlate with superior persistence ( Inostroza et al., 2020 ). However, in these studies the root systems were physically constrained during growth, leading to, at minimum, compromised estimates of root length densities and other metrics across the depth profile.…”
Section: Discussionmentioning
confidence: 99%
“…Root mesocosms, typically large horticultural pots or long narrow pipes form which the entire root system can be extracted, have proven useful in understanding RSA and root function of several agricultural species. For examples: it was reported that a lower number of crown roots in maize can be beneficial for nitrogen acquisition in poor nitrogen soils ( Saengwilai et al., 2014 ), a moderate progressive drought could lead to RSA adaptations in various rice cultivars that improve performance under reduced water management practices ( Hazman and Brown, 2018 ), some Green Revolution wheat progenitors have smaller root systems than older landraces ( Waines and Ehdaie, 2007 ), and Chilean red clover cultivars with certain RSA traits, such as high crown root diameter and low branching index, correlate with superior persistence ( Inostroza et al., 2020 ). However, in these studies the root systems were physically constrained during growth, leading to, at minimum, compromised estimates of root length densities and other metrics across the depth profile.…”
Section: Discussionmentioning
confidence: 99%
“…This insight could be considered as empirical evidence of the drought tolerance improvement transferred from M. arborea to M. sativa . Tani et al [ 18 ], showed that at seedling stage, alborea hybrids exhibited higher stem elongation rate, photosynthetic rate, stomatal conductance, and transpiration rate (E) than sativa and arborea accessions under drought stress, indicating that the hybrids correspond to a drought tolerance ideotype [ 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ShootDM (an estimator of forage yield) forage yield was significantly associated with SLA, leaf size and StemD, which coincide with results of other works [ 36 ]. From an agronomic point of view, the alfalfa LSratio has been used as a positive estimator of forage quality, owing to the greater quality of leaves relative to stems [ 32 , 37 , 38 ]. The LSratio performed as a differentiator trait of the agronomic categories identified by the cluster analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In SSS, the mixed sward increased its RDW accumulation and RLD during the entire growing season, relative to DSS (Figure 1; Table 4). This is a common response of plants growing under marginal soil conditions to increase the soil foraging capacity and capture of soil resources (Acuña et al., 2016; Acuña & Inostroza, 2013; Inostroza et al., 2020; Inostroza, Acuña & Méndez, 2015 ; Inostroza & Acuña, 2010; Lynch, 2019). Inostroza et al.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, RLD is narrowly related with root diameter. Greater RLD species tend to have greater plasticity in root growth and greater physiological capacity for water and nutrient uptake (Fitter, 2002; Inostroza et al., 2020).…”
Section: Discussionmentioning
confidence: 99%